Evaluation of KRAS, NRAS and BRAF mutations detection in plasma using an automated system for patients with metastatic colorectal cancer. - Claire Franczak; Andréa Witz; Karen Geoffroy; Jessica Demange; Marie Rouyer; Marie Husson; Vincent Massard; Céline Gavoille; Aurélien Lambert; Pauline Gilson; Nicolas Gambier; Julien Scala-Bertola; et al. (PLoS ONE, 2020)
Background Cell-free DNA detection is becoming a surrogate assay for tumor genotyping. Biological fluids often content a very low amount of cell-free tumor DNA and assays able to detect very low allele frequency mutant with a few quantities of DNA are required. We evaluated the ability of the fully-automated molecular diagnostics platform Idylla for the detection of KRAS, NRAS and BRAF hotspot mutations in plasma from patients with metastatic colorectal cancer (mCRC). Materials and methods First, we evaluated the limit of detection of the system using two set of laboratory made samples that mimic mCRC patient plasma, then plasma samples from patients with mCRC were assessed using Idylla system and BEAMing digital PCR technology. Results Limits of detection of 0.1%, 0.4% and 0.01% for KRAS, NRAS and BRAF respectively have been reached. With our laboratory made samples, sensitivity up to 0.008% has been reached. Among 15 patients' samples tested for KRAS mutation, 2 discrepant results were found between Idylla and BEAMing dPCR. A 100% concordance between the two assays has been found for the detection of NRAS and BRAF mutations in plasma samples. Conclusions The Idylla system does not reach as high sensitivity as assays like ddPCR but has an equivalent sensitivity to modified NGS technics with a lower cost and a lower time to results. These data allowed to consider the Idylla system in a routine laboratory workflow for KRAS, NRAS and BRAF mutations detection in plasma.